2023
DOI: 10.1186/s12916-023-03042-y
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in antenatal care: recent insights and advances

Jessica Atkinson,
Roxanne Hastie,
Susan Walker
et al.

Abstract: Background For decades, antenatal care in high-resource settings has involved 12–14 face-to-face visits across pregnancy. The COVID-19 pandemic forced many care providers to rapidly embrace telehealth to reduce face-to-face visits. Here we review recent advances in telehealth used to provide antenatal care. Main body We conducted a narrative review examining the impact of telehealth on obstetric care. Two broad types of telehealth are used in anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Additionally, multiple studies have shown that prenatal telegenetic consultations are as accurate and effective in conveying information as in-person consultations. 31,[38][39][40] Patients have high levels of satisfaction with virtual visits and appreciate the convenience, personalized interactions, and the ability to involve family members in discussions without logistical challenges. 37 When compared with in-person genetic service delivery, most patients reported reduced anxiety and high level of knowledge.…”
Section: Acceptability Of Telehealth Servicesmentioning
confidence: 99%
“…Additionally, multiple studies have shown that prenatal telegenetic consultations are as accurate and effective in conveying information as in-person consultations. 31,[38][39][40] Patients have high levels of satisfaction with virtual visits and appreciate the convenience, personalized interactions, and the ability to involve family members in discussions without logistical challenges. 37 When compared with in-person genetic service delivery, most patients reported reduced anxiety and high level of knowledge.…”
Section: Acceptability Of Telehealth Servicesmentioning
confidence: 99%
“…Through telehealth, a drastic reduction in adverse intrapartum and postpartum outcomes, which may have been associated with delayed care initiation due to poor access to a caregiving facility, has been witnessed. 41 Additionally, telemedicine is set to replace most in-person antenatal and postpartum supervisory care. For example, antenatal care models recommend at least 14 antenatal care contacts for low-risk pregnancies; telehealth offers a platform supplementing physical care sessions, consequently cutting down on the cost of accessing healthcare facilities and the resultant loss of work hours.…”
Section: Bridging Health Disparities: the Role Of Digital Healthmentioning
confidence: 99%
“…For example, antenatal care models recommend at least 14 antenatal care contacts for low-risk pregnancies; telehealth offers a platform supplementing physical care sessions, consequently cutting down on the cost of accessing healthcare facilities and the resultant loss of work hours. 39 , 41 - 43 …”
Section: Bridging Health Disparities: the Role Of Digital Healthmentioning
confidence: 99%
“…ACOG classifies the telehealth models into three broad categories, namely, synchronous (real-time), asynchronous (sending medical imaging for later interpretation), or remote monitoring [ 34 ]. The COVID-19 pandemic accelerated the adoption of telehealth services for pregnant women, proving to be both safe and cost-effective.…”
Section: Reviewmentioning
confidence: 99%